Review—Corrosion-Resistant High-Entropy Alloy Coatings: A Review. Issue 11 (9th November 2021) - Cheng, Hongxu; Pan, Zhimin; Fu, Yu; Wang, Xuefei; Wei, Ya; Luo, Hong; Li, Xiaogang
Abstract : For a long time, the corrosion problem of materials has been an essential factor in restricting high-tech and national economic development. As an effective means of corrosion protection, surface coatings have drawn extensive attention in the field of material corrosion. Performance improvement and a new composition system of high-entropy alloys (HEAs) have made HEA coatings a research hotspot. HEA coatings inherit the "four core effects" of bulk HEAs, especially high entropy and sluggish diffusion, making high-quality coatings exhibit outstanding corrosion resistance. At present, many reports have focused on the performance of HEA coatings in the field of severe corrosion environments. This article reviews the process parameters and different element contents on the corrosion resistance of HEA coatings in recent years. This paper describes the advantages and excellent corrosion resistance of HEA coatings, including the preparation methods and classification of HEA coatings. Moreover, exploration of the corrosion behavior and the mechanism of HEA coatings are described, and the influence of passivation behavior and microstructure change on the corrosion resistance of HEA coatings are discussed. Finally, the prospect of research on corrosion-resistant HEA coatings is proposed, and possible future research directions and ideas are suggested.